Alat Analisis Strategi Bertahan Hidup Sektor Informal Perkotaan Selama Pandemi Covid-19: Review Literatur - M.Akmal Farraz; Adha Fathiah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
The covid-19 pandemic has damaged the structure of the global economy, including Indonesia. Government policies that are stuttering and inconsistent between handling health or economic recovery have resulted in their implementation being not optimal and having a significant impact on economic actors in the informal sector. As a result, informal workers need to make efforts to survive amid the crisis. Based on a literature review, this article presents analytical concepts for analyzing strategies undertaken by young informal workers with an illustration of informal sector workers in the city of Banda Aceh. The results show that there are seven possible ways to survive in the midst of the covid-19 pandemic, namely taking debt to family and friends, returning to your hometown, reducing the quantity of consumption, working with other people's capital, building a subsistence economy, diversification of informal workers and circumventing government regulations. These strategies are rooted in everyday life and in reality which are taken for granted and therefore are not acts of instrumental rationality.